Optimal Policies in Dual Economies - Basu, Kaushik C. (Quarterly Journal of Economics, 1980)
Journal Article Optimal Policies in Dual Economies Get access Kaushik C. Basu Kaushik C. Basu Delhi School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 95, Issue 1, August 1980, Pages 187–196, https://doi.org/10.2307/1885356 Published: 01 August 1980